In Quest of SME-Conducive Policy Formulation - J. Hanns Pichler (Entrepreneurial Business and Economics Review)
Objective:The article focuses on the role of SMEs in the national, regional and global environment. The main objective of the article is to present the economic and social importance of SMEs in the context of policy formulation for their support and development.